(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
In our modern world, people from all walks of life and all demographics agree that education is crucial. In today’s knowledge-driven society, everyone needs access to high-quality education if they want to thrive. The special educators benefitted from the training they received, which allowed them to provide their low vision children with appropriate functional vision instruction. Utilizing Low Vision Devices for Scanning - Teachers have difficulties while trying to scan with poor vision equipment. Students’ expectations are low since low vision. Understanding the kind and degree of the student’s visual impairment will allow you, as a teacher, to provide the most appropriate help.